Learning Style and Students’ Achievement in English for Profession Course of IT Education Department - Ayu Rizki Septiana; Moh Hanafi (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2023)
This research was aimed at investigating students’ learning style, investigating students’ achievement on English for Profession Course and seeing whether there is significant difference on students’ achievement across different learning style. This research used a convergent mixed method design. The data were taken using questionnaire of learning style and achievement test. The findings of this study showed that from 37 students, 17 students were auditory learners, 15 students were visual learners and 5 students were kinesthetics learners. Further, the mean score of achievement test for auditory and visual learners showed that they can be categorized into good achievement while the mean score of kinesthetics learners showed that they can be categorized into very good achievement. Here, the visual learners have the lowest mean score of 80.67 and the kinesthetics learners have the highest mean score of 86.00. Meanwhile, the auditory learners were in between with 82.35 of mean score. Finally, one-way Anova analysis is used to test the hypothesis and it showed that the Fcount < Ftable (0.335 < 3.28). Thus, H0 is accepted and it can be concluded that there is no significant difference on students’ achievement in English for Profession course across the three learning styles of auditory, visual and kinesthetics.